Interactive Language Acquisition: Merging Activities and Technology (Architecture Image Studies, 2025)
Pandit Jawaharlal rightly said, “English is the window to the world”. English became the tool that opens windows to the world, expands our minds to the latest technologies and unlocks doors to opportunities. This is not a sudden ascent of English to this position, but a gradual change. It is being used for more distinct and varied purposes than before. English in India is not just a language to be learnt but the base for whole learning process at all levels starting from schools to universities. As all other professional courses are adapted to the present day’s industrial needs, so is English language. In addition to the above changes, the competencies which are expected from global professionals, particularly of technical and business fields have changed the boundaries of English – learning processes. We have witnessed history as we stood the threshold of the 21st century, biding adieu to the last and welcoming a new era altogether. This is an era of globalization where man has witnessed tremendous development in the field of technology. With the world turning into one global village, the modern man has developed the need of a global language. One of the major forces of globalization in India has led to an overwhelming demand for engineers across the globe. The last few years have witnessed an unprecedented rise in the number of skilled professionals in India, employed by both local and multi-national companies. With the whole world becoming one global market and result-oriented, professionals are facing new challenges in effective communication every day. Students of professional colleges require an ever-increasing range of skills to maintain relevance with the global environment of the new millennium. So proficiency in English enables the individuals to land better jobs in business and industry. That is why, there is a great demand for English and it has a lot of “surrender value”. It provides good social status in the community and we need English in the present-daycontext to be the bridge between us and the outside world. F.G.French said, “By accidents of history and by the rapid spread of industrial development, science and technology, international trade and by something like an explosion in the speed and ease of travel and by the factors which have been broken frontiers and forced nations into closer inter-dependence English has become a world language. It has opened world-wide chances for employment.” The object of this paper is to suggest some interactive activities in order to instill interest among students in learning English for equipping them with the essential skills. It enables and enhances learner’s proficiency in the use of English language as a means of self-expression in real life situations. The teacher has to introduce the Integrated Skills approach in the classroom that means teaching all the language skills weaved in one activity, is an accepted panacea for the problems faced by the teachers to cope with the time and need-based courses. Introduce the activities which aim to motivate and meet the needs of the learners.